Oral hygiene conditions and perception of oral health among adolescents in institutional care: a pilot study (Research, Society and Development, 2022)
The oral cavity is the gateway to the body and to maintain oral health it is necessary to adopt adequate hygiene measures, resulting in an impact on the individual's quality of life and well-being. Adolescence is marked by vulnerability due to the individual's growth and development. It is also during this phase that oral health can be left in the background. These difficulties are intensified among those who live in a more fragile context, especially in the foster care situation. This research aimed to know the conditions of oral hygiene and perception of oral health among young people in foster care. Carried out in Recife, Brazil, this is a pilot, cross-sectional, quantitative study, with a sample of forty adolescents in institutional foster care, aged 10 to 17 years. Most adolescents (62.5%) reported that in the last 30 days they brushed their teeth 3 times a day. About the self-perception of oral health, although most adolescents (85%) reported that they felt well or very well about their oral health, almost a third (27.5%) reported feeling frequently embarrassed when smiling. Most of the interviewees are male (67.5%) and are in the age group of 14 to 17 years (75%). It is concluded that adolescents reported performing oral hygiene regularly, as well as reported feeling good about their oral health conditions, however, a significant portion of adolescents reported feeling at some point, shame when smiling.